2001
DOI: 10.1002/qua.1038
|View full text |Cite
|
Sign up to set email alerts
|

Quadrupole coupling constants CQQ for 2H, 27Al, and 17O atoms calculated at the periodic Hartree–Fock level for understanding the geometry of H‐form aluminosilicates

Abstract: ABSTRACT:The coordinates of crystallographically different atomic types of Si-O(H)-Al Brönsted centers within five H-form aluminosilicate frameworks-ABW, CAN, CHA, EDI, and NAT-were optimized using a full periodic ab initio Hartree-Fock scheme at the STO-3G level. Single-point calculations were then carried out at the ps-21G * (Al, Si)/6-21G * (O, H) and 6-21G * (Al, Si)/6-21G * (O, H) levels to obtain the 2 H, 27 Al, and 17 O respective nuclear quadrupole coupling constants and electrostatic field gradient an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 67 publications
(117 reference statements)
2
14
0
Order By: Relevance
“…This closer agreement of the AlOH distances for HCHA optimized using CRYSTAL even at minimal STO-3G level is corroborated by the good agreement with experimental quadrupole coupling constants C qq of 27 Al ranging between 11 Figure 3 of Ref. [22], which is out of the experimental interval of 11-17 MHz [19 -21].…”
Section: Geometries Of Optimized H-form Structuressupporting
confidence: 80%
“…This closer agreement of the AlOH distances for HCHA optimized using CRYSTAL even at minimal STO-3G level is corroborated by the good agreement with experimental quadrupole coupling constants C qq of 27 Al ranging between 11 Figure 3 of Ref. [22], which is out of the experimental interval of 11-17 MHz [19 -21].…”
Section: Geometries Of Optimized H-form Structuressupporting
confidence: 80%
“…The authors mentioned that factor (3) is, however, negligible for C qq ( 17 O), but not for C qq ( 2 H) 16. The latter was also confirmed for the OH moieties in H‐form aluminosilicates, for which a good agreement with known experimental C qq ( 2 H) values for relevant systems was proved at the PHF/ps‐21G*(Al, Si)/6‐21G*(O, H) level 18 owing to the inharmonic elongation of the OH bridged group. Unfortunately, to our knowledge any correlation between the C qq ( 17 O) or the electric field gradient (EFG) anisotropy and the HOH bond angle of H 2 O was never discussed.…”
Section: Introductionsupporting
confidence: 65%
“…Let us remark that, in another work 22 we also calculated the |EF(H)| values at the protons of bridged hydroxyl moieties for a series of PHF‐optimized H‐form aluminosilicates (ABW, CAN, CHA, EDI, and NAT) 18, 33, 34 as well as for ABW borosilicates 22. Comparing the values, we observe that the |EF(H)| values for the various zeolite framework hydroxyl protons are different; the values range from 0.05 as for HNAT to 0.005 E h /(e × a.u.)…”
Section: Resultsmentioning
confidence: 99%
“…As we have shown above, the most important MM, i.e., the dipoles on O atoms and octupoles on the T atoms, can be well presented with the linear form at the 6‐21G* level. This basis set level should also be sufficient for the computation of the electrostatic field gradients on framework 17 O, 2 H, 27 Al atoms 31, as it has been shown that the close 6‐31G* basis set provides correct values of NMR shielding constants 35. Two evident problems, however, appeared herein with the a priori most suitable minimal STO‐3G basis set [its suitability is suggested, without showing it here, for example, by the nice linear behavior (6) of the O quadrupole \documentclass{article}\pagestyle{empty}\begin{document}$Q^{m}_{2}$\end{document}(O) and Si hexadecapole \documentclass{article}\pagestyle{empty}\begin{document}$Q^{m}_{4}$\end{document}(Si) components].…”
Section: Discussionmentioning
confidence: 99%
“…Further improvements of the basis set level should thus be checked on the basis of the closeness between other calculated values and experimental data. In this sense in another work 31, we have shown a good agreement between the experimental (for “large”‐size zeolites) and calculated (for “small”‐size zeolites) quadrupole coupling constants C qcc of the 17 O, 2 H, and 27 Al atoms, which confirms the correct values of the gradient field on these atoms. Further similar steps should be considered to reach a better coincidence with the measured electrostatic field too 3, 4.…”
Section: Approximations Of the Multipole Moments For Aluminosilicate mentioning
confidence: 97%